The fourth R : conflicts over religion in America's public schools - DelFattore, Joan, 1946- (New Haven : Yale University Press, 2004)
"Traces the evolution of school-prayer battles from the early 1800s, when children were beaten or expelled for refusing to read the King James Bible, to current disputes over prayer at public-school football games ... Explores the enduring tension between people of goodwill who wish the schools to promote majoritarian beliefs, and equally well-meaning (and often religious) people who deplore any government influence in religious matters"--jacket.
Crucible -- The past that never was -- Religion as a team sport -- Off the streets and into the courts -- Stalin and school prayer -- The myth of Madalyn Murray O'Hair -- Picnic with a tiger -- Beware of the leopard -- Full court press -- The rest is silence -- Caution! Paradigms may shift -- Perkins's last stand -- Mississippi learning -- The school and the rabbi -- Zen and the art of constitution maintenance -- Deliver us from evil -- Appendix. Advocacy groups.
Includes bibliographical references (p. 325-329) and index.
Keywords: Religion in the public schools -- United States